Do Human Capital and Export Diversification Decline or Augment CO$_{2}$ Emissions? Empirical Evidence from the MINT Countries - Joof, Foday; Isiksal, Aliya Zhakanova (Journal of Environmental Accounting and Management, 2026)
This paper analyzes the consequence of human capital and export diversification on the CO$_{2 }$emissions of Mexico, Indonesia, Nigeria and Turkey (MINT). To attain the impartiality of the study, the Pooled Mean Group (PMG) is used on panel data from 1975-2010. The outcome from the PMG reveals that education (human capital) has a negative consequence on CO$_{2}$ in the long term. This indicates that an increase in education reduces the level of CO$_{2}$ emissions in the environment. Furthermore, export diversification is positively associated with carbon emissions in the long run. The findings also illustrated that the environmental Kuznets curve (EKC) hypothesis is invalid for these nations. The outcomes of Dumitrescu and Hurlin (DH) causality provided evidence for unidirectional causation running from export diversification to CO$_{2}$ emissions. Also, a feedback association amid human capital and CO$_{2}$ emissions is found. However, economic expansion, the quadratic term of GDP, and energy consumption have no causal association with carbon emissions.